2003
DOI: 10.1046/j.1460-9592.2003.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Programming Optimal Atrioventricular Delay in Dual Chamber Pacing Using Peak Endocardial Acceleration: Comparison with a Standard Echocardiographic Procedure

Abstract: Optimization of programmed atrioventricular delay in dual chamber pacing is essential to the hemodynamic efficiency of the heart. Automatic AV delay optimization in an implanted pacemaker is highly desirable. Variations of peak endocardial acceleration (PEA) with AV delay at rest correlate well with echocardiography derived observations, particularly with end-diastolic filling and mitral valve closure timings. This suggests the possibility of devicing a procedure for the automatic determination of the optimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 19 publications
(32 reference statements)
0
32
0
2
Order By: Relevance
“…Cardiac Resynchronization Therapy (CRT) is indicated for patients suffering from drug-refractory congestive heart failure (CHF) associated with inter-ventricular dyssynchrony [1]. The implantation of a bi-ventricular stimulator makes it possible to re-synchronize the electrical activation of both ventricles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac Resynchronization Therapy (CRT) is indicated for patients suffering from drug-refractory congestive heart failure (CHF) associated with inter-ventricular dyssynchrony [1]. The implantation of a bi-ventricular stimulator makes it possible to re-synchronize the electrical activation of both ventricles.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the peak to peak amplitude of first component of the EA signal (EA1) is well correlated to the maximum rate of rise of left ventricular pressure [8] and has been successfully used to optimize CRT [1].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with complete AV block and an implanted DDD pacemaker, Ritter et al reported a highly significant difference between the optimal AV delay obtained by echocardiography and that obtained by the peak endocardial accel- eration (PEA) method, which corresponds to the 'knee' of the PEA curve vs the AV delay. 20,21 PEA is detected by a ventricular lead equipped with a micro-accelerometer. Various reports have shown that PEA is synchronous with S1.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our first step of evaluation should be to optimize the AV delay [32][33][34] in the pacemaker and CRT population.…”
Section: Potential Clinical Applicationsmentioning
confidence: 99%